The Impact of Transformational Leadership, Work Motivation, and Organizational Culture on Civil Servant Performance: An Empirical Study in Indonesian Local Government - Hairun Zainuddin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study analyzes the influence of transformational leadership, work motivation, and organizational culture on Civil Servant (ASN) performance at the Department of Youth and Sports, Luwu Regency, Indonesia. Four hypotheses were tested: transformational leadership, work motivation, and organizational culture each positively affect ASN performance, and all three variables simultaneously affect performance. A quantitative explanatory approach with cross-sectional survey design was employed. Using a census technique, all 31 ASN at the agency served as respondents. Data were collected via a structured 48-item Likert-scale questionnaire adapted from established instruments, including the Multifactor Leadership Questionnaire, Perry public service motivation scale, Denison Organizational Culture Survey, and Pradhan and Jena performance scale. Multiple linear regression with SPSS was used for analysis, preceded by classical assumption tests. Results show that transformational leadership, work motivation, and organizational culture each have a positive and significant effect on ASN performance, and all three variables jointly explain a substantial proportion of performance variance, confirming all four hypotheses. Transformational leadership emerged as the strongest predictor, underscoring the critical role of inspirational and individually considerate leadership in public sector performance. These findings suggest that agency leaders should prioritize transformational leadership development, strengthen intrinsic and public service motivation, and foster an organizational culture centered on involvement, adaptability, and clear mission. Future research should explore mediating variables such as employee engagement or job satisfaction, and apply structural equation modeling for deeper causal analysis.